Valoración de propiedades mecánicas y de durabilidad de concreto adicionado con residuos de llantas de caucho (2014)
The results presented in this document are part of the master's degree project in Civil Engineering, with emphasis on structures, the purpose is to assess the mechanical properties and durability of concrete with replacement of rubber tires, partially replacing the fine aggregate in volume. For the development of the work four types of mixtures were prepared, the first without the addition of rubber grain, the second replacing 10% of the fine aggregate with the same amount in rubber volume, the third and fourth mixture in the same way but with Replacement percentages of 20% and 30% respectively. The mechanical properties were evaluated as: resistance to compression and flexion; durability tests such as: penetration of chlorides, carbonation, absorption and electrical properties such as resistivity and impedance. The mechanical and durability tests were evaluated at ages of 28 and 90 days and in the case of compressive strength the samples were tested at 3, 7, 28 and 90 days. Finally, it is concluded that the resistance to compression and bending decreases with the addition of rubber in the mixture. Regarding durability tests: the penetration of chlorides in RCPT tests increases with the percentages of 20% and 30% of rubber addition, however for 10% the penetration decreases with respect to the sample with 0% replacement in tests performed at 90 days, for the tests carried out with the NTBUILD-492 method the penetration of the chloride ion is directly proportional to the increase in percentage of rubber substitution; the increase in carbonation depth values ​​are directly proportional to the increase in percentage of rubber addition; With respect to the values ​​of surface absorption, these decrease with the partial replacement of rubber for ages of 28 days, however this behavior is reversed for tests performed at 90 days, with better performance samples with less percentage of rubber substitution. Finally, it is concluded that the electrical properties of each mixture are unique and vary with respect to the age of the test and the speed at which the electric current circulates through the samples, likewise the resistivity of the samples decreases with the increase in percentage of rubber addition.